Know Where You Stand: Affective Effects of Becoming Aware of a Place's National Socialist History - Ries, Melissa; Schwan, Stephan (Frontiers in Psychology, 2022)
Visiting historical places can give important impulses regarding education of history, society, and politics. While there does exist extensive research on visitors' experiences at memorial sites, little is known about the impact of everyday places holding dark history. Two experimental studies took place in a research institute, a former women’s clinic, where in the time of National Socialist (NS) dictatorship in Germany hundreds of forced sterilizations took place. Historical awareness was manipulated via systematic variation of prior information. We found partial evidence that historical awareness had a negative effect on personal mood. Awareness of the site’s NS history had a negative effect on the perceived valence of related photos but did not influence their qualitative description. Also, there was partial evidence that the site itself was perceived less positively and evoked more arousal when participants were aware of its NS history. Possible reasons are discussed.